Circulating Human Neonatal Naïve B Cells are Deficient in CD73 Impairing Purine Salvage - Pettengill, Matthew Aaron; Levy, Ofer (Frontiers in Immunology, 2016)
Background: Extracellular purines, in particular adenosine (Ado) and adenosine-triphosphate (ATP), are critical immunoregulatory molecules. Expression and activity of purine ecto-enzymes on B cells in neonatal and adult blood may influence their function and has been incompletely characterized. Methods: Mononuclear cells were isolated from human neonatal (cord blood) or adult (peripheral blood) subjects and evaluated directly by flow cytometry for expression of purine ecto-enzymes. Additionally, B cell subsets were isolated from mononuclear cell fractions by fluorescence-activated cell sorting and gene transcription of purine ecto-enzymes (CD39 and CD73), adenosine deaminase (ADA1), purine nucleoside phosphorylase (PNP) and select purine receptors (A2a) were evaluated by reverse transcription followed by qRT-PCR. Immuno-magnetic-bead isolated naïve B cells were evaluated for enzymatic activity by incubation with radio-labeled purines followed by thin-layer chromatography, and subsequent B cell Ado acquisition was evaluated by liquid scintillation quantitation of radio-labeled Ado uptake. Results: Relative to their adult counterparts, neonatal circulating naïve B cells were markedly and selectively deficient in CD73 as observed by gene transcription, surface protein expression, and enzyme activity. Neonatal naïve B cell deficiency of CD73 expression significantly impaired their capacity to acquire extracellular purines for purine salvage. Conclusions: Human neonatal circulating naïve B cells are selectively deficient in CD73, impairing extracellular purine acquisition and potentially contributing to impaired B cell responses in early life.